Mao. 20 - Takahashi, Rumiko, 1957-; Roman, Annette (Viz Media, LLC, 2025)
"Mao and Nanoka attempt to save Soma both from the beast that possesses him and his own worst impulses. Natsuno continues training Nanoka to wield the power of the earth but can't stop her apprentice from pushing herself too far. Then Mao is spirited away, and Byoki makes a move. The question remains--where is Daigo's soul?"--